Increased systemic immune-inflammation index predicts hemorrhagic transformation in anterior circulation acute ischemic stroke due to large-artery atherosclerotic. (3rd June 2023) - Yang, Yi; Han, Yanfei; Sun, Weidong; Zhang, Yongbo
Abstract: Background and Purpose: Inflammation and immune response play an important role in hemorrhage transformation after acute ischemic stroke. According to previous studies, systemic immune-inflammation index is associated with severity of stroke. We aimed to evaluate the association between systemic immune-inflammation index and hemorrhage transformation in anterior circulation acute ischemic stroke due to large-artery atherosclerosis. Methods: This was a retrospective analysis of patients with anterior circulation acute ischemic stroke due to large-artery atherosclerosis. The laboratory data were collected within 24 h after admission. Hemorrhage transformation was defined on follow-up magnetic resonance imaging or Computed Tomography. The univariate analysis and multivariate logistic regression were performed to assess the association of systemic immune-inflammation index with hemorrhage transformation. Then the relationship between systemic immune-inflammation index and hemorrhage transformation in different stroke subtypes was further studied. Results: We included 310 Chinese anterior circulation acute ischemic stroke patients due to large-artery atherosclerosis (mean age 65 ± 11.4 years; 72.6% male). Hemorrhage transformation occurred in 41 patients (13.2%). After multivariate regression analyses, systemic immune-inflammation index (odds ratio [OR] 1.109, 95% Confidence Interval [CI] 1.054–1.167, p ＜0.001) was independently associated with hemorrhage transformation. Systemic immune-inflammation index was found to be significantly related to hemorrhagic transformation in artery-to-artery embolization (OR 1.111, 95% CI 1.029–1.210, p ＜0.001) and in-situ thrombosis (OR 1.059, 95% CI 1.011–1.194, p = 0.045). Conclusions: Higher systemic immune-inflammation index is associated with greater risk of hemorrhagic transformation in patients with anterior circulation acute ischemic stroke due to large-artery atherosclerosis, especially in artery-to-artery embolization and in-situ thrombosis.